MODIFIKASI DONGKRAK ULIR BOTOL MENGGUNAKAN MOTOR LISTRIK - Islami, Syaiful; Fauzi, Muhammad Ridha (SURYA TEKNIKA, 2022)
The jack is the main equipment that must be present when driving a car. The presence of a jack is very important in the event of a tire leak or other damage that requires the jack to be operated. The operation of the jack is very difficult if the operator is an elderly person, a disabled person or a woman. Therefore, it is necessary to modify the mechanical jack into an easier electric jack. The purpose of this study was to modify a manual bottle screw jack into an electric jack to make it easier for the operator or driver if the car needs to be lifted using a jack. The modified jack is a type of bottle screw jack using an electric motor. The modification of the jack is done using a DC motor as the main driver to replace human power and other components. The load test was carried out using a Mitsubishi Colt T with a weight of 1000 Kg. The results show that the modified jack helps to reduce the difficulty in operation, reduce time, increase efficiency.